DEVELOPMENT OF DIGITAL TECHNOLOGY TOWARDS CONSTRUCTION SAFETY COMPLIANCE IN INDONESIA - Fatmasari Faisal, Ulfa; Fansuri, Ilham (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2023)
It is known that currently digital development is very rapid and has great benefits in helping to make construction work easier and more efficient. With the benefits it has, the construction industry is also not immune from developments in digital technology, such as fulfilling construction safety. Based on Minister of PUPR Regulation No.10/2021, in implementing SMKK it must meet Security, Safety, Health and Sustainability Standards. Fulfillment of these standards ensures construction engineering safety, occupational health and safety, public safety and environmental safety. This study will discuss technological developments towards fulfilling Construction Safety by referring to the substance of the SMKK and K4 Standards that have been established. Based on this, data collection was carried out based on construction projects in Indonesia through scientific journals, proceeding papers, books, and/or related official websites. The data is then processed using descriptive analysis to obtain patterns or descriptions of technological developments related to construction safety in Indonesia. It was concluded that the development of digital technology related to construction safety has been developed and implemented in Indonesia. However, there are still other aspects of construction safety that could be opportunities for further research. There is also limited information regarding the fulfillment of construction safety that can be accessed in general, so further research is needed to find out more comprehensive developments in construction safety technology